2019
DOI: 10.1111/ctr.13532
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in HIV+/HCV+ coinfected kidney transplant recipients in the pre‐ and post‐direct‐acting antiviral therapy eras: 10‐Year single center experience

Abstract: Background: Previous studies have demonstrated inferior patient and graft survival following kidney transplant (KT) in HIV+/HCV+ coinfected patients compared to HIV+/HCV− recipients. However, these studies were conducted prior to the availability of direct-acting antiviral (DAA) agents and data in the modern era are lacking. Methods: Single center retrospective study of HIV+/HCV+ coinfected KT recipients (2007-2017). Outcomes were assessed for the pre-DAA and post-DAA (ie, after December 2013) eras including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In the general transplant population, treatment of HCV infection has been associated with improved patient and allograft survival (25). One small study from Miami (26) suggests that the same is true among transplant recipients coinfected with HIV/HCV. In a cohort of 13 patients with HIV/HCV who were transplanted from 2007 to 2017, patient (100% versus 83%) and allograft (100% versus 67%) survival were significantly better in those treated with DAAs and cured of their HCV infection.…”
Section: Addressing Hcv Coinfectionmentioning
confidence: 99%
“…In the general transplant population, treatment of HCV infection has been associated with improved patient and allograft survival (25). One small study from Miami (26) suggests that the same is true among transplant recipients coinfected with HIV/HCV. In a cohort of 13 patients with HIV/HCV who were transplanted from 2007 to 2017, patient (100% versus 83%) and allograft (100% versus 67%) survival were significantly better in those treated with DAAs and cured of their HCV infection.…”
Section: Addressing Hcv Coinfectionmentioning
confidence: 99%
“…Treatment of HCV may be key to improving transplant outcomes for patients co‐infected with HIV/HCV. A series of 13 HIV/HCV co‐infected kidney transplant recipients from Camargo et al 26 demonstrated 100% patient and allograft survival in recipients cured of HCV after transplant, whereas patient survival was only 83% and allograft survival 67% in the pre–direct‐acting antiviral (DAA) era. The optimal timing for HCV treatment in HIV+/HCV+ patients depends mostly on the severity of liver disease and local waiting time.…”
Section: Hiv and Eskdmentioning
confidence: 99%
“…Contemporary cohorts of HIV-infected transplant recipients have demonstrated excellent patient and graft survival [1][2][3][4][5][6][7]. Similarly, for patients with hepatitis C virus (HCV) infection, kidney transplantation offers a survival benefit and can be more cost-effective than remaining on the waitlist [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-DAA era, transplantation in patients coinfected with HIV and HCV was associated with reduced graft survival and higher rates of serious infection [25]. However, recent small case series showed improved outcomes, including fewer infectious complications, in coinfected patients treated with DAA after transplant [3,4,6].…”
Section: Introductionmentioning
confidence: 99%